Assessing energy expenditure and exercise intensity in horizontal jumps by heart rate monitoring - Veligekas, P.; Theodoru, A. S. (Journal of Human Movement Studies, 2006)
The aim of the present study was to assess training exercise intensity and energy expenditure (EE) during long and triple jumps performance. Twelve high level long and triple jumpers (8 males and 4 females), a week prior to their participation in a major competition, had their VO2max and HRmax predicted by a Polar S810i and then performed a training session which included performing maximal jumps. A mean of 14.2±4.1 jumps were performed interspersed with a 3.50±0.84 minutes interval. Mean and peak Jump intensities were 83.2±2.9% and 85.8±2.8% of HRmax. Mean and peak jump EE for males (n=8) were 0.152±0.025Kcal /kg min and 0.219±0.029Kcal/ kg min respectively while for females (n=4) were 0.135±0.01 Kcal/ kg min and 0.198±0.016Kcal / kg min respectively. The EE per jump was significantly negatively correlated to relaxation rate (-0.613, p<0.01), while the mean intensity per jump significantly negatively correlated to interval duration (-0.629, p<0.01) and positively correlated to relaxation rate (0.833, p<0.01). Recording long and triple jump heart rate under training conditions, for the purposes of exercise intensity and energy expenditure prediction, permits useful evaluations regarding the work done and efficient training interventions.